NATIONALISM IN ISLAMIC LITERATURE : (Study of Mustafa al-Ghalayaini’s thought in Izzat al-Nasyi’in) - Mumtaz, Nadhif Muhammad; Azmi, Muhammad Bagus; Khoiriyah, Siti (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2023)
Zamakhsari Dhofier said that the Islamic classic book became the crucial component of Indonesia's Pesantren (Islamic boarding school). Various Islamic classic books were used to determine orientations of education in the Pesantren. However, all these orientations lead to one main goal: to create qualified Muslims. This condition caused the weakness of nationalist character in the pesantren environment; even at the next level, it could produce radical movements. This is due to the absence of classic Islamic books explaining that a Muslim must have a nationalist character. The available literature is only oriented toward making Muslims as good Muslims, not as good citizens. The book Izzat al-Nasyi'in, written by Mustafa Al Ghalayaini, specifically came with nuances of nationalist character. This study aims to elaborate on the contents of the Izzat al-Nasyi'in. This qualitative research uses a socio-historical approach with an analytical descriptive method. The technique used is content analysis. The results of this study show that according to Mustafa Al Ghalayaini in Izzat al-Nasyi'in, morality (Akhlaq) is related not only to the divine aspect but also to nationalism aspects. He explained that one of the pillars to become a civilized country and a prosperous society is the existence of a nationalist character. So, He included the nationalist character as an integral part of a moral (Akhlaq) education. Izzat al-Nasyi'in is necessary to be applied in every Pesantren in Indonesia.